Low vision matters [large type] : a practical guide to living with low vision & blindness - Stevens, Laura J., 1945- (Square One Publishers, 2025)
"The book is divided into two parts. Part One focuses on the day-to-day activities that low vision can affect-from safety in your home or traveling outside, to the handling of finances or one's home entertainment system. It discusses the latest technologies that can enable a person with eyesight problems to turn on a light, start a dishwasher, or even answer a phone through the use of oral commands-and that's just the tip of the iceberg. Part Two then provides a breakdown of the various kinds of helpful vision-aid products now available. Because the authors understand the costs involved in purchasing such equipment, they include the names of those organizations and associations in an extensive Resources section along with various other crucial contacts about which those with low vision and their loved ones and caretakers need to know"--